2010
DOI: 10.3389/fnsys.2010.00032
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in functional nodes of the brain cortex - a high model order group ICA study

Abstract: Functional MRI measured with blood oxygen dependent (BOLD) contrast in the absence of intermittent tasks reflects spontaneous activity of so-called resting state networks (RSN) of the brain. Group level independent component analysis (ICA) of BOLD data can separate the human brain cortex into 42 independent RSNs. In this study we evaluated age-related effects from primary motor and sensory, and, higher level control RSNs. One hundred sixty-eight healthy subjects were scanned and divided into three groups: 55 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 42 publications
4
30
1
1
Order By: Relevance
“…The analysis for the differences between groups was carried out using an FSL dual regression technique that allows for voxel-wise comparisons of resting-state fMRI (Filippini et al, 2009; Littow et al, 2010; Veer et al, 2010; Abou Elseoud et al, 2011). This involves (A) using the group-ICA spatial maps in a linear model fit against the separate fMRI data sets, resulting in matrices (time-course matrices) describing the temporal dynamics for each component and subject, and (B) using these time-course matrices to estimate subject-specific spatial maps.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis for the differences between groups was carried out using an FSL dual regression technique that allows for voxel-wise comparisons of resting-state fMRI (Filippini et al, 2009; Littow et al, 2010; Veer et al, 2010; Abou Elseoud et al, 2011). This involves (A) using the group-ICA spatial maps in a linear model fit against the separate fMRI data sets, resulting in matrices (time-course matrices) describing the temporal dynamics for each component and subject, and (B) using these time-course matrices to estimate subject-specific spatial maps.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis for the differences between groups was carried out using an FSL dual regression technique that allows for voxel-wise comparisons of resting-state fMRI (Filippini et al, 2009; Littow et al, 2010; Veer et al, 2010; Abou Elseoud et al, 2011). This involves (A) using the group-ICA spatial maps in a linear model fit against the separate fMRI data sets, resulting in matrices (time-course matrices) describing the temporal dynamics for each component and subject, and (B) using these time-course matrices to estimate subject-specific spatial maps.…”
Section: Methodsmentioning
confidence: 99%
“…Such observations motivate consideration of whether the seeds employed by earlier studies map to distinct functional subdivisions of the DMN whose anti-correlation patterns differ substantially, given the growing evidence that the DMN is functionally heterogeneous. With independent component analysis (ICA), several groups have revealed that the DMN splits into dorsal and ventral branches (Damoiseaux et al, 2008; Shirer et al, 2012), or more subdivisions depending on the specified component numbers (Damoiseaux et al, 2008; Damoiseaux et al, 2012; Littow et al, 2010; Shirer et al, 2012; Westlye et al, 2011). (Uddin et al, 2009) also observed heterogeneous subdivisions within the DMN by placing seeds in MPFC and PCC respectively.…”
Section: Introductionmentioning
confidence: 99%